Invitro Effect of Bulkfill and Incremental Application Techniques with Different Composite Filling Materials on Marginal Microleakage - Albahari, Aulfat A.; Madfa, Ahmed A.; Dubais, Mohammed A. (University of Science and Technology, Yemen, 2020)
Objective: To assess the in vitro effect of bulkfill and incremental application techniques on the microleakage of class II dental cavities filled with three different bulkfill composite materials at occlusal and cervical margins. Methods: Standardized class II cavities were prepared on 120 human premolar teeth extracted for orthodontic treatment, which were randomly divided into two main groups of 60 teeth, corresponding to the two application techniques. Each group wasthen sub-dividedrandomly into three sub-groups based on the type of bulkfill restorative materials as follows: TetricN-Ceram BulkFill, FiltekBulkFill flowable restorative material and X-trafilBulkFill. All cavities were prepared and etched, and the corresponding self-etch bond adhesive systems were applied. A stereomicroscope was used to assess microleakage after thermocycling and immersion of the specimens in 0.1% methylene blue for 24 hours. Mann-Whitney U test was then used to analyze data. Results: No statistically significant difference was found in the marginal microleakage between the incremental and bulkfill techniques using the three types of composite materials at both occlusal and cervical margins. The X-trafilBulkFill showed the lowest score of microleakage with both application techniques compared to other bulkfill composite materials. Conclusion: Both incremental and bulkfill application techniques using TetricN-Ceram BulkFill, FiltekBulkFill flowable restorative material and X-trafilBulkFill composite materials have a comparable effect on the marginal microleakage at occlusal and cervical margins of human teeth extracted from dental clinics in Sanaa city. Further studies are recommended to assess the clinical success of bulkfill composite materials using SEM or confocal microscope.